AKTIVITAS MANUSIA PENDUKUNG DI CERUK GUA GONG BARAT, JIMBARAN, BALI - Heri Purwanto (Journal Social and Humaniora, 2017)
Prehistoric man made cave as a favorite place to take shelter. Moreover, it can also as a place to move. It can be traced from the traces left behind. Ceruk Gua Gong Barat located in preparation environment Angga Swara Nongkong stone, Desa Adat Jimbaran, Badung, Bali showed traces of prehistoric human activities. Namely residential activity, hunting and gathering, processing foodstu?s. Indications of such activities based on various archaeological findings in the form of shells, animal bones, animal teeth, fish bones, and shaved. Keywods: Gua Gong niche West, Prehistoric Human Activity